Diagnostic value and forensic relevance of a novel photorealistic 3D reconstruction technique in post-mortem CT - Böven, Judith (Br J Radiol, 2020)
OBJECTIVES: Evaluation of performance and forensic relevance of a novel, photorealistic, 3D reconstruction method (cinematic rendering, (CR)) in comparison with conventional post-mortem CT (PMCT) and volume rendering (VR) technique for visualization of traumatic injuries. METHODS: 112 pathologies (fractures, soft tissue injuries and foreign bodies) from 33 human cadavers undergoing whole body PMCT after traumatic death were retrospectively analyzed. Pathologies were reconstructed with CR and VR techniques. Fractures were classified according to their dislocation. Images were evaluated according to their expressiveness and judicial relevance by two forensic pathologists using a five-level Likert-scale (1: high expressiveness, 5: low expressiveness). They decided whether CR reconstructions were suitable for judicial reviews. The detection rate of pathologies was determined by two radiologists. RESULTS: CR was more expressive than VR for all three trauma categories (p < 0.01) and than conventional CT when used for fractures with dislocation (p < 0.001), injuries of the ventral body surface (p < 0.001), and demonstration of foreign bodies (p = 0.033). CR and VR became more expressive with a higher grade of fracture dislocation (p < 0.001). 20% of all pathologies in the CR and VR reconstructions were not detectable by radiologists. CONCLUSION: CR reconstructions are superior to VR regarding the expressiveness. For fractures with substantial dislocation, soft tissue injuries, and foreign bodies in situ, CR showed a significantly better expressiveness than conventional PMCT. CR and VR have significant limitations in cases of fractures with minor dislocations and covered soft tissue injuries. ADVANCES IN KNOWLEDGE: CR is a helpful tool to present pathologies found in PMCT for judicial reviews.